Revolution and counter-revolution in the Cossack’s village of Cherlakovskaya. 1918–1928 - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
The history of the Revolution of 1917 and the Civil War in Russia continues to attract the interest of modern historians and sociologists. The socio-economic transformations of the end of the XX century and the development of the methodology of history led to an increase in the relevance of questions about land use and land ownership, the emergence of new assessments and approaches to solving them. The aim of the study is to determine the causes and level of participation of the Cossacks and other groups of the population of the village Celakovsky in the events of the Revolution and the Civil War, as well as the participation of the сossacks in the solution of the agrarian question in the territories controlled by the сossacks. Using archival materials, memoirs of contemporaries and local history studies, the author comes to the conclusion that the front-line cossacks, who did not want to continue the war and supported the Soviet government in the fall of 1917, mostly sabotaged its agrarian transformations on the ground. By the summer of 1918 The cossack’s population of the village opposed the redistribution of the cossack lands on the basis of the decree on socialization, and supported the overthrow of the Soviet government. Further agrarian transformations became possible only after the victory of the bolsheviks in the Civil War